Influence of Raw Materials on Optical Properties of Bi-doped PrFeO3 - Luxová, Jana; Šimková, Lenka; Šulcová, Petra (Česká společnost průmyslové chemie, 2019)
In this work, the orthoferrites based on PrFeO3 doped by Bi were investigated as inorganic pigments. The samples with chemical formula BixPr1-xFeO3 (x=0-0.3) were synthetized by solid state reaction and an influence of different raw material source of Fe3+ (Fe2O3 and FeOOH) was studied. Calcination process was performed at 1000°C and 1100°C with maintaining for 3 hours. The particle size distribution was measured by the device Mastersizer 2000/MU (Malvern Instr., GB). The phase composition was verified by the X-ray diffraction analysis using Miniflex 600 (Rigaku, Japan) and the phase identification of studied powders was achieved with a program that using matching of the diffraction patterns with data by the ICDD-PDF2 database. A heating microscope with automatic image analysis EM201-12 (Hesse-Instruments, Germany) was used for study of the thermal stability. The greatest attention was focused on determination of the colour properties. Colour properties of the powders and pigments applied into organic binder were studied with using device ColorQuest XE (HunterLab, USA). The results have shown that the utilization of a suitable Fe3+ raw material has a significant effect on the colour properties of the orthoferrites. Pigments prepared from FeOOH were significantly darker with a lower contribution of the red colour. Shades were brown to red-brown. In contrast, pigments prepared from Fe2O3 showed brighter orange to reddish orange shades.
Vliv surovin na optické vlastnosti PrFeO3 dopovaného Bi
Keywords: Perovskite; Inorganic pigments; Colour properties; Phase composition; Solid state reaction; Perovskity; anorganické pigmenty; barevné vlastnosti; fázové složení; reakce v pevné fázi